Context sensitive health informatics : sustainability in dynamic ecosystems - Marcilly, Romaric; Kuziemsky, Craig E.; Nøhr, Christian; Pelayo, Sylvia (Studies in health technology and informatics, 2019)
The digital transformation of healthcare delivery remains a work in progress, and contextual variation continues to be one of the barriers to the development of sustainable health information technology. Context-sensitive health informatics concerns health information technologies and their environments, which may be people such as patients, users, designers and evaluators, but also non-human constructs such as organizations, work practices, guidelines and protocols, or buildings and markets. This book presents papers from CSHI 2019, the international conference on Context Sensitive Health Informatics, held in Lille, France, on 23 and 24 August 2019. The subtitle of the conference was Sustainability in Dynamic Ecosystems, and the thirty papers included here are divided into six sections: understanding organizational contexts; towards sustainable EHR; different contexts for medication errors and patient safety; methods and models to study contexts for health information systems; citizens in health contexts; and designing and evaluating in contexts. Two keynote speeches from the conference are also included. With its focus on context sensitivity and sustainability in digital healthcare, the book will be of interest to all those working in the field of health informatics.